ChemInform Abstract: Asymmetric Synthesis of α‐Amino Acids under Operationally Convenient Conditions. Issue 52 (29th December 2014) - Joerres, Manuel; Chen, Xia; Acena, Jose Luis; Merkens, Carina; Bolm, Carsten; Liu, Hong; Soloshonok, Vadim A.
Abstract A new chiral Ni(II)—complex (I) is synthesized from proline‐derived amide, glycine, and Ni(NO3)2.